LIGHT EMITTING DIODE (LED) HIJAU DAN PENGARUHNYA TERHADAP PENGURANGAN BYCATCH PENYU PADA PERIKANAN GILLNET DI PERAIRAN PALOH (Green Light Emitting Diode (LED) and its Effect on Sea Turtle Bycatch Reduction of Gillnet Fisheries in Paloh Waters) - Ganang Dwi Prasetyo; Ronny Irawan Wahju; Roza Yusfiandayani; Mochammad Riyanto (Bogor Agricultural University, 2017)
ABSTRACTBycatch problem is a global issue and can be a driver of marine megafauna declines in the world, such as sea turtle, where is the animal's status as endangered species. Green Light Emitting Diode (LED) is known as an innovative technology to reduce sea turtle bycatch without reduce target catch effectively. The use of green LED in order to reduce sea turtle bycatch in gillnet fisheries was carried out in Paloh Coast, West Borneo during August to October 2015. Experiment performed a total of 20 settings with gillnet fleets operate two units simultaneously, ie gillnet control (without LED lights) and gillnet experiment (with LED lights). Turtles caught predominantly were in the juvenile phase as 57.14% and the potential location of capture sea turtle bycatch in station 2 (1˚52' - 1˚56' LU and 109˚14' - 109˚18' BT). The results, showed that the green turtle (Chelonia mydas) were caught of 7 turtles, were captured by control gillnet 6 turtles with an CPUE 0.29 ± 0.03 Turtle/E, while by experimental gillnet 1 turtle with an CPUE by 0,04 ± 0,009 Turtle/E. The used of green LED light was significantly reduce sea turtle bycatch of 85% without decreasing target catch.Keywords: CPUE, green LED light, sea turtle bycatchABSTRAKPermasalahan terkait bycatch merupakan isu utama global yang dapat mengancam penurunan populasi megafauna laut seperti penyu yang telah berstatus endangerd species. Lampu LED merupakan inovasi teknologi untuk mengurangi bycatch penyu tanpa mengurangi hasil tangkapan ikan utama secara efektif. Penggunaan lampu Light Emmitting Diode (LED) hijau untuk mengurangi bycatch penyu pada perikanan jaring insang (gillnet) dilakukan di perairan Paloh, Kalimantan Barat selama bulan Agustus hingga Oktober 2015. Uji coba dilakukan dengan menggunakan 2 unit kapal gillnet yang dioperasikan di setiap stasiun pengamatan secara bersamaan dengan jumlah ulangan sebanyak 20 kali, diantaranya gillnet kontrol (tanpa lampu LED) dan gillnet eksperimen (dengan lampu LED). Penyu yang tertangkap cenderung didominasi oleh fase juvenile sebesar 57,14% dan lokasi potensi tertangkapnya bycatch penyu pada stasiun 2 (1˚52' - 1˚56' LU dan 109˚14' - 109˚18' BT). Hasil penelitian menunjukkan bahwa penyu yang tertangkap merupakan penyu hijau (Chelonia mydas) berjumlah 7 ekor, terdiri dari 6 ekor tertangkap pada gillnet kontrol dengan CPUE 0,29 ± 0,03 ekor/E, dan 1 ekor pada gillnet eksperimen dengan CPUE 0,04 ± 0,009 ekor/E. Penggunaan lampu LED hijau memberikan pengaruh secara significant untuk mengurangi bycatch penyu dengan persentase pengurangan sebesar 85% tanpa mengurangi hasil tangkapan ikan utama.Kata kunci: CPUE, lampu LED hijau, bycatch penyu